Mental Health Crisis in the Digital Era: The Role of Mass Media in Increasing Awareness and Access to Services - Rahmah, St.; Susilo, Catur Budi; Ermawan, Budi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The development of technology and mass media has had an impact on people's mental well-being. One of them is the increasing prevalence of mental health disorders, such as depression and anxiety, which are directly related to social media use, work pressure, and the social isolation that results from digital life. The aim of this research is to examine the role of mass media in increasing awareness and access to mental health services. The research method used is descriptive analysis with a qualitative approach, involving surveys and interviews with respondents representing various age groups and social backgrounds. Data were collected to evaluate the extent to which mass media provide accurate and educational information about mental health and facilitate access to appropriate support services. The research results show that mass media has an important role in increasing public awareness about mental health issues. Articles, television programs and online campaigns have succeeded in turning negative stigma into a broader understanding of mental health. In addition, the media also plays a role in promoting available mental health services, such as counseling and therapy, thereby increasing accessibility for individuals who need them. The conclusion of this research confirms that mass media has great potential to be an effective tool in overcoming the mental health crisis in the digital era. By providing appropriate and educational information and facilitating access to mental health services, mass media can act as an agent of positive change in an effort to improve people's mental well-being. Therefore, cooperation between the government, health institutions and mass media is very important to create a supportive environment for individuals who experience mental health problems in this digital era.